An investigation on the use of alternative shapes to determine the applicable strain energy function for nearly-incompressible hyperelastic materials - Senador, Antonio E. (1999)
Different assumptions on the nature of the mechaninsm involved in the deformation of hyperelastic materials have led to a number of different proposals for the functional form of the strain energy function. The proponents of each form employed different methods to fit their function on the experimental data, and they used different measures to assess the capability of these fitted models to predict the material behavior in other deformation modes. This investigation proposes another measure for assessment, which would subsequently lead to the selection of the best strain energy function to represent the actual material behavior.